Causes and Outcome of Children with Lower Gastrointestinal Bleeding (LGIB) Presenting at Tertiary Care Hospital - Yasir Ali, Shafqat Huma, Noman Dilshad, Irfan Ullah, Muhammad Khalid, James Watt, Zaibullah Khan, Farida Gul, Hina Farooq, Muhammad Ibrahim Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: One of the most potentially fatal pediatric events is gastrointestinal (GI) bleeding. Lower gastrointestinal bleeding children often have anemia, but determining the cause of the bleeding is crucial in developing a management plan. Objective: To assess the causes and outcome of children presenting with lower gastrointestinal bleeding. Methodology: The current study was prospective cross sectional study carried out at the pediatrics department of Fauji Foundation Hospital, Peshawar Cantt for duration of one year from June 2021 to July 2022. A total of 250 children with lower GI bleeding were enrolled in the current study. All the data was analyzed by IBM SPSS version 23. Results: In the current study, male children were 140 (56%) while female children were 110 (44%) with the mean age of 6.80 (± 1.50) years. The commonest complaint was abdominal pain in 105 (42%) patients whereas the commonest clinical observation was pallor observed amongst 115 (46%) patients. Juvenile colonic or rectal polyps were observed in 91 (36.4%) patients based on colonoscopy. Based on histo-pathological findings, polyps were observed in 93 (37.2%) patients, amongst whom 90 (96.77%) cases were Juvenile polyps and 3 (3.33%) cases were familial adenomatous polyposis. Conclusion: There are several underlying causes of lower gastrointestinal bleeding (LGIB). Abdominal pain was a common symptom in children with LGIB while the most typical cause of LGIB in children was a juvenile polyp in our study. Colonoscopy is a safe and effective diagnostic and therapeutic technique for children with LGIB. Keywords: Children; Lower gastrointestinal bleeding; Causes; Outcomes